Marazm czy wykorzystana szansa? Społeczności lokalne wobec działań samorządów lokalnych w warunkach członkostwa Polski w UE i decentralizacji kraju (Politeja, 2015)
Fatigue or fulfilled opportunity? Local communities facing local self‑government policy in light of Poland’s EU membership and decentralisationThe article below is a response to the question about consequences of two milestones of contemporary Polish history to the local communities. These two events of the latest history are significant: 15 years since the territorial reform and introduction of three‑leveled regional authority and the 10th anniversary of Polish membership in the European Union. Based on the researches and replies to the questions of the respondents we are allowed to address an issue not only of potential successes and benefits connected with the mentioned events but also all failures, which create discomfort in existence of local communities in their homeland. The author presents an attitude of citizens of 6 Polish municipalities to the European Union as well as the most important advantages and disadvantages of Polish participation in the structures of the EU (connotations to the EU, satisfaction from drawdown European funds and the matter of introducing common currency to Polish economics). Data from the surveys will be confronted with the perspective of respondents to low public administration, predominantly in municipalities (an ability to absorb EU funds with all the consequences such as debts, decisions consulting, satisfaction from civil service along with the most common pathologies).